Pemanfaatan Media Sosial, Kreativitas dan Modal Usaha Terhadap Keberlanjutan Usaha Ladu Arai Pinang Di Kampung Perak Kecamatan Pariaman Tengah - likanopa syentia; Anisa Putri Nabila; Dwi Fuji Wahyuni; Ridho Deza Perkasa (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2025)
The influence of social media, creativity and business capital is very important to effect the sustainability of Alai Pinang Ladu MSMEs in Central Pariaman District. The method of this research is quantitative descriptive. The sampling technique used is purposive sampling. The sample of this study was 55 respondents, the data collection method used the distribution of questionnaires or questionnaires. The data analysis techniques used are multiple linear regression, t-test, F-test, and determination coefficient. Based on the results of multiple linear regression is Y= 46.820 – 0.377X1 + 0.194X2 + 0.304X3 + e. From the results of the t-test, it was found that social media had a negative effect on business sustainability in Ladu Arai Pinang MSMEs in Central Pariaman District. Creativity has a positive and significant effect on business sustainability in Alai Pinang Ladu MSMEs in Central Pariaman District, business capital has a positive and significant effect on business sustainability in Alai Pinang Ladu MSMEs in Central Pariaman District. The results of the F test were obtained that social media, creativity, and business capital together have a positive and significant effect on business sustainability in Adu Arai Pinang MSMEs in Central Pariaman District. The result of the determination coefficient was 50.5%.